2020
DOI: 10.1101/2020.12.10.419242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The combined treatment of Molnupiravir and Favipiravir results in a marked potentiation of antiviral efficacy in a SARS-CoV-2 hamster infection model

Abstract: Since its emergence in Wuhan, China in December 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread worldwide resulting in a global pandemic with >2 million deaths within a year of the emergence of the virus. In the search for small molecule inhibitors of SARS-CoV-2 Molnupiravir (EIDD-2801), an orally bioavailable nucleoside analog that was originally developed as an antiviral against influenza viruses but that exerts also activity against a number of other RNA viruses, includi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…With the efficacy of molnupiravir unaffected by mutations in VoCs B.1.1.7 and B.1.351, and taking into consideration that molnupiravir showed promising initial results in a phase 2 clinical trial in COVID-19 patients, this compound could potentially be a panlineage SARS-CoV-2 antiviral agent as more VoCs emerge in the future. Recently, we reported on the potent antiviral effect of the combination of molnupiravir and favipiravir in the SARS-CoV-2 hamster infection model [ 7 ]. By employing it as part of combination therapy, concerns for the development of resistance to molnupiravir when this drug is used alone could be greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the efficacy of molnupiravir unaffected by mutations in VoCs B.1.1.7 and B.1.351, and taking into consideration that molnupiravir showed promising initial results in a phase 2 clinical trial in COVID-19 patients, this compound could potentially be a panlineage SARS-CoV-2 antiviral agent as more VoCs emerge in the future. Recently, we reported on the potent antiviral effect of the combination of molnupiravir and favipiravir in the SARS-CoV-2 hamster infection model [ 7 ]. By employing it as part of combination therapy, concerns for the development of resistance to molnupiravir when this drug is used alone could be greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The molecule exerts its antiviral activity via incorporation into viral RNA, resulting in the accumulation of deleterious transition mutations in the nascent viral RNA, leading to error catastrophe [ 5 ]. Molnupiravir (EIDD-2801, MK-4482), the orally bioavailable prodrug counterpart of N 4 -hydroxycytidine [ 6 ], is effective against SARS-CoV-2 infections in Syrian hamsters [ 7 ], mice [ 8 ], and ferrets [ 9 ]. Data from a first-in-human, phase 1, randomized, double-blind, placebo-controlled study in healthy volunteers indicate that the drug is well tolerated and that plasma exposures exceed the expected efficacious doses based on scaling from animal models [ 10 ].…”
mentioning
confidence: 99%
“…The model is well-suited to assess the impact of antiviral drugs as we and others have demonstrated. Notably, we have demonstrated that Favipiravir and Molnupiravir (EIDD-2801) markedly reduce SARS-CoV-2 replication in hamsters, whereas hydroxychloroquine does not (14,15).…”
Section: Main Textmentioning
confidence: 99%
“…The model is well-suited to assess the impact of antiviral drugs as we and others have demonstrated. Notably, we have demonstrated that Favipiravir and Molnupiravir (EIDD-2801) markedly reduce SARS-CoV-2 replication in hamsters, whereas hydroxychloroquine does not (14,15). Six to eight weeks female Syrian Golden hamsters were treated with Nelfinavir (15 mg/kg/dose or 50 mg/kg/dose) or the vehicle control by intraperitoneal injection (IP) within one hour before intranasal infection with 50 µl containing 2x10 6 TCID50 of SARS-CoV-2 [BetaCov/Belgium/GHB-03021/2020 (EPI ISL 109 72 407976|2020-02-03)] (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…There has been some recent promising data from small clinical trials for proxalutamide treatment in men with COVID-19, another anti-androgen [22,23], and for molnupiravir, a repurposed anti-viral therapy (EIDD-2801) originally tested against influenza. Molnupiravir appears effective in-vitro and in-vivo models against COVID-19 [44], and preliminary data from small clinical trials showed improved rates of viral clearance in humans [42]. No export and drug price data for both molnupiravir and proxalutamide were found.…”
Section: Aspects For Further Researchmentioning
confidence: 99%